Beyond Beasts: Some Cases of Native American AniManism - Rauniyar, Bijay Kumar (Literary Studies, 2020)
We all are animals and animals (are) us. There is only a thin line between both of us and beasts. We often tend to fall towards the beastly line. This paper, however, will show how the Native American tribes maintain their ties and wisdom with the animals. For them, animal spirits stand for life and livelihood. They regard animals as “the messenger for wisdom about life, nature, and power. These also prophecy future (events), as we take dogs’ moaning to herald earthquake and cats’ growling to trumpet troubles. The tribes represent those spirits through symbols on clothes, art and ceremonial items as “Traditional Ecological Knowledge,” or TEK, in short (Grayson). For example, northern Plains peoples used buffalo images in holy rites and placed its skulls on homes to honor its spirit while others name clans after animals, and use animal amulets, talismans, and fetishes. In Nepal also, some Tharus have Gajaraj (King of Elephants) clan; and Hatti (elephant) is the clan name of a Vaishya caste in Terai. Here Gaindakot, across the Trishuli River, is named so as “a habitat of rhinos” and Chitrawan (Chitwan) after Chitrakut, India and it celebrates the entire flora and fauna along with the humans. Other noteworthy animal place names, among many, are Gaighat (Udaypur), Bayalbas (Sarlahi), Ghodasahan (Bihar, India), Gaushala (Mahottari and Kathmandu), Gauchar(an) (Kathmandu), Singapore (Singapore), and so on. Many deities have animals as their carriers or costumes like snake and tiger skin (Shiva), mouse (Ganesha), and peacock (Saraswati), and many nations have animals as their prominent national symbols like eagle (USA), tiger (India), lion (Sri Lanka). Even some currencies carry animals denoting denominations—for examples, gainda (rhino) means 100.00 NPR, bagh (tiger) stands for 500.00 NPR, and hatti (elephant) is worth 1,000.00 NPR.